ナンキョク ショウワキチ ニ オケル エンチ ジシン ノ ケンチリツ 1987～2007 - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (2010)
P(論文) 南極・昭和基地(69.0°S,39.6°E)では,短周期,長周期の各3成分のアナログ及びデジタル記録による地震記象の読み取り作業が,1967年以降現在まで継続されている.インテルサット衛星回線の導入に伴い,2005年度以降は国立極地研究所へ自動伝送されたデジタルデータを用いた読み取りも併用している.P,PKP,PP,S,SKS等の地震波走時と震源データは,アメリカ地質調査所(USGS)と国際地震センター(ISC)へ定期的に送られると共に,"JARE Data Reports (Seismology)" として発刊されている.本稿では,1987年より2007年の21年間における験震データを用いて,昭和基地の地震モニタリング観測で記録された遠地地震の空間分布と時間的推移を調べた.特に震源パラメータについて,地震の深さ依存性やマグニチュード検知レベルの季節変動を考察した.またISCデータを用いたグローバル観測網の結果と比較して,南半球の地震検知率について議論した. A phase identifying procedure for the teleseismic events at Syowa Station (69.0°S, 39.6°E), Antarctica has been carried out since 1967 by use of analog and digital records of short- and long-period seismometers. After the establishment of an INTELSAT telecommunication link, several kinds of digital data have been transmitted to the National Institute of Polar Research (NIPR) for the utilization of seismic phase identification. The arrival times of several phases, such as P, PKP, PP, S, SKS have been reported to the United States Geological Survey (USGS) and International Seismological Center (ISC), then published as the "JARE Data Reports (Seismology)". In this paper, hypocentral distribution and time variations for the detected earthquakes by monitoring observation at Syowa Station was studied in the 21 year period from 1987 to 2007 by using the published Data Reports. The epicental parameters were investigated in terms of focal depth dependency and seasonal trending in the threshold range of detectable magnitude. Moreover, the detection capability of teleseismic events in the southern hemisphere was discussed in comparison with global results derived from ISC data. departmental bulletin paper